A Mixed- Method Analysis of Communication Styles, Conflict Management and Personal Growth Initiative in Long Distance and Proximal Romantic Relationships - Varaich, Palack Deep Kaur (My University, 2024)
This study explores communication styles, conflict management strategies, and personal growth initiatives in long-distance relationships (LDRs) compared to proximal relationships. Utilizing a mixed-method approach, qualitative interviews were conducted first, followed by quantitative analysis. The sample for interviews consisted of 10 males and 10 females in LDRs. Subsequently, quantitative data were collected from 20 males and 20 females in long-distance relationships, as well as 40 males and 40 females in proximal relationships. The qualitative phase involved in-depth interviews with participants, while the quantitative phase utilized structured surveys assessing communication skills, conflict management, and personal growth initiative. Initial analysis of quantitative data revealed noteworthy differences in communication patterns and conflict resolution strategies between long-distance and proximal relationships. Qualitative findings illuminated themes such as trust, communication challenges, and personal growth opportunities in LDRs, while proximal relationships emphasized physical proximity and immediate conflict resolution. This research contributes valuable insights to both theoretical understanding and practical applications for individuals navigating diverse relationship contexts.
Keywords: Communication styles; ,Conflict management, Personal growth initiative; Distance maintenance behaviors.; Relationship satisfaction,Trust